Low-density high-performance heat-conducting structural adhesive for power battery and preparation method thereof
By introducing modified hollow glass microbeads and aluminum hydroxide into the thermal conductivity glue of the power battery, a nano-scale network structure with enhanced cross-linking reaction is formed, which solves the problem that thermal conductivity glue in the prior art is difficult to meet the thermal conductivity, mechanical strength and low density at the same time. , the balance between low density and high thermal conductivity of the thermal adhesive layer is achieved.
Patent Information
- Application Number
- CN202411269429.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-29
- Filing Date
- 2024-09-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The polyurethane thermal conductivity glue in the prior art is difficult to meet the requirements of thermal conductivity, mechanical strength, flame retardancy and low density of power batteries at the same time, resulting in a contradiction between the thermal conductivity coefficient and density.
By introducing modified hollow glass microbeads and aluminum hydroxide, a nano-scale network structure with enhanced cross-linking reaction and long chain interpenetration is formed to build a micro-network structure of the thermally conductive glue layer, so that the thermally conductive glue layer has low density and high thermal conductivity.
The balance between low density (not greater than 1.50 g/cm3) and high thermal conductivity coefficient (not less than 0.84W/(m•k)) of the thermal conductivity layer is achieved, and the density, mechanical strength, high thermal conductivity, and resistance of the thermal conductivity layer are overcome. The conflicting performance of combustion and other performances meets the needs of weight loss and efficiency improvement for electric vehicles.
Smart Images

Figure CN119410322A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of power battery manufacturing, and specifically relates to a low-density, high-performance thermally conductive structural adhesive for a power battery and a preparation method thereof. Background Art
[0002] Thermally conductive adhesive, also known as thermally conductive structural adhesive or thermally conductive sealant, is a material with high thermal conductivity. It can quickly transfer heat from one surface to another. It is usually used as an efficient tool for heat transfer. It is usually composed of polymer materials and thermally conductive fillers. Its main function is to improve the efficiency of heat conduction and is used for thermal management and heat dissipation. There are many types of thermally conductive adhesives for power batteries on the market. Thermally conductive adhesives can be synthesized from a variety of materials and can be divided into silicone thermally conductive adhesives, epoxy thermally conductive adhesives, acrylate thermally conductive adhesives, polyurethane thermally conductive adhesives, etc. according to their main materials.
[0003] Power batteries are one of the core components of electric vehicles, which directly affects performance and driving range. With the continuous development and growth of the electric vehicle market, power battery technology is also constantly innovating and improving. Lithium-ion batteries have the advantages of small size, high energy density, long cycle life, and low environmental pollution. They are gradually replacing lead-acid batteries. Their applications in consumer electronics, electric vehicles, energy storage devices, etc. are gradually deepening. The market demand is large and maintains rapid growth. The power lithium batteries of electric vehicles currently mainly use ternary lithium-ion battery technology. Ternary lithium-ion batteries have the advantages of high energy density, long cycle life and low self-discharge rate, and are widely used in the field of electric vehicles. With the rapid development of electric vehicles, higher requirements are also put forward for lithium battery thermal conductive structural adhesives. On the one hand, it is necessary to support automobile weight reduction and consumption reduction, and on the other hand, it is also necessary to have high comprehensive performance, good heat dissipation performance, mechanical properties and environmental aging resistance. However, the thermal conductive structural adhesives in the existing technology cannot meet the above requirements at the same time.
[0004] Polyurethane thermal conductive adhesives in the prior art are often used to seal and bond adjacent automotive power lithium battery module shells, as well as to effectively seal and bond lithium battery module shells and boxes, and must have good thermal conductivity, mechanical strength, flame retardancy, etc. However, there are some common problems with existing polyurethane thermal conductive adhesives, including: to improve the thermal conductivity, it is necessary to increase the amount of thermal conductive powder filler, which leads to problems such as high material viscosity, high density, and overall weight gain; if the amount of thermal conductive powder filler is reduced, it will lead to problems such as reduced thermal conductivity and poor flame retardancy; if the thermal conductivity is increased by adding nitrides, there will be problems such as high material viscosity and high price; the low-density and high-thermal conductive polyurethane structural adhesives in the prior art can usually only reduce the density to 1.6 g / cm 3For example, the Chinese invention patent document CN114316880A discloses a low-density, high-thermal-conductivity polyurethane structural adhesive, which is composed of component A and component B, and the weight ratio of component A to component B is 1: (0.8-1.2). Component A includes: castor oil-modified polyol, polyester polyol, polyether polyol, dispersant, yellow toner, catalyst, aluminum hydroxide, dehydrating agent, silane coupling agent, fumed silica, defoaming agent; component B includes: low-viscosity castor oil-modified polyol, isocyanate, molecular sieve, dispersant, monofunctional isocyanate, fumed silica, silane coupling agent, low-density filler, blue toner, thermal conductive filler; the potting glue has the characteristics of low density, low modulus, high strength, and high thermal conductivity, but its density is 1.6 g / cm 3 The thermal conductivity is 0.8~0.9W / (m·K), and in particular, it must use a thermally conductive filler with excellent performance. After replacing other thermally conductive fillers, the thermal conductivity is significantly reduced and the product viscosity is significantly increased; for example, after replacing with (organic material) expanded microspheres, the system density increases, so the expanded microspheres selected by the invention can have a lower density, and the minimum solid density recorded in the embodiment is 1.62g / cm 3 However, the thermal conductivity is only 0.82W / (m·K) at this time, so it is difficult to take into account the requirements of reducing material density and maintaining key properties such as thermal conductivity.
[0005] Chinese invention application CN 202311417045.4 discloses a low-density two-component polyurethane thermal conductive structural adhesive for power batteries and a preparation method thereof. The structural adhesive recorded in Example 1 is composed of component A and component B with a volume ratio of 1:1. The formulas of both components A and B use Sanlight HS28 glass microspheres (hollow glass microspheres, D50=45μm, =0.28g / cm 3 , compressive strength 28MPa / 4000psi) 1.5 parts by weight, the total addition amount is 3wt%, and the corresponding density of the structural adhesive after curing is 1.61g / cm 3 , thermal conductivity is 1.22W / (m·K), and the tensile strength of the body is 8.4MPa; Examples 1-3 all reduce the density by adding glass microspheres, and at the same time appropriately increase the content of thermal conductive powder to compensate for the loss of thermal conductivity, and finally achieve a balance between density and thermal conductivity. Therefore, in the technical solution of this invention, the added glass microspheres are mainly to reduce the density and achieve a balance between density and thermal conductivity without having other functions and technical effects. Due to the large diameter of the glass microspheres and the small addition ratio, the adhesive layer of 1cm after curing 3 The number of microbeads contained is 2.60 The area occupied by each microbead (calculated as a square) is , 1cm 3The average number of microbeads in each layer of the glue layer is 11,700. The minimum distance between the edges of two glass microbeads in the glue layer is 92.45-45=47.45μm, which is larger than the diameter of the glass microbeads. The pores between two adjacent glass microbeads are large and it is difficult to form the skeleton of the glue layer. Therefore, a large amount of thermal conductive powder is required to fill the pores, making the overall addition of thermal conductive powder exceed 70wt%, the thermal conduction path is longer, and there is an abnormal density trend: when the addition of glass microbeads is 2wt%, the density of the glue layer is 1.58g / cm 3 When the addition amount increases to 3wt%, the density is 1.61g / cm 3 As the amount of hollow microspheres added increases, the density of the adhesive layer increases instead of decreasing. When the maximum addition amount is 6wt%, the density is 1.60g / cm 3 , the density of the 2wt% addition also keeps rising. In addition, due to its low compressive strength, the hollow glass microspheres of HS28 (D50=45μm) have a greater risk of breaking and a relatively high breakage rate during production and use. The increase in the breakage rate will inevitably lead to an increase in the density of the adhesive layer and a decrease in the thermal conductivity and mechanical strength.
[0006] In summary, the glass beads added to the polyurethane thermal conductive adhesive in the prior art are mainly for adjusting the density. They cannot participate in the formation of a specific microstructure or shorten the heat conduction path during the curing process of the adhesive layer. The density of the thermal conductive adhesive layer after curing is still contradictory to the mechanical strength, high thermal conductivity, flame retardancy, adhesion, etc. Therefore, it is difficult for the existing technology to take into account the above-mentioned properties at the same time, and it is difficult to meet the needs of weight reduction and efficiency improvement of electric vehicles at the same time. Summary of the invention
[0007] In view of the above-mentioned deficiencies of the prior art, a low-density, high-performance thermal conductive structural adhesive for power batteries and a preparation method thereof are provided. By synergistically improving the raw materials and the preparation method, organic materials with unique components and proportions are introduced to polymerize into long-chain polymer materials, and hollow glass microspheres and aluminum hydroxide (both of which have the function of shaping the microscopic network structure) with appropriate scales, strengths and addition ratios are introduced, and the components are coordinated with each other to construct the microscopic network structure in the thermal conductive adhesive layer with a sufficient number of modified hollow glass microspheres as the skeleton; during the curing process, the hollow glass microspheres, aluminum hydroxide and the polymer material jointly form a nanoscale network structure with enhanced cross-linking reaction and long-chain interpenetration, so that two adjacent modified hollow glass microspheres are The pore distance between the edges of the glass microbeads is smaller than the diameter of the modified hollow glass microbeads. The polymer material can effectively encapsulate the inorganic thermal conductive filler aluminum hydroxide powder particles and the modified hollow glass microbeads, shortening the length of the three-dimensional thermal conductive path around the modified hollow glass microbeads, so that the cured thermal conductive adhesive layer forms an interpenetrating network and a three-dimensional thermal conductive structure at the nano-micrometer scale, and significantly reduces the solid density of the thermal conductive adhesive layer while maintaining or improving other key properties. The thermal conductive adhesive layer can maintain thermal conductivity, insulation, flame retardancy, high strength and excellent toughness, thereby overcoming the contradictory properties of the density of the thermal conductive adhesive layer and mechanical strength, high thermal conductivity, flame retardancy, adhesion, etc., so as to simultaneously meet the needs of weight reduction and efficiency improvement of electric vehicles.
[0008] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A low-density, high-performance thermally conductive structural adhesive for a power battery, which is made of the following components in the following proportions by weight: Component A: polyol 20-40, small molecule alcohol 0.5-2.0, dehydrating agent 0.1-1, aluminum hydroxide 60-75, catalyst 0.01-0.10, modified hollow glass microspheres 3-13; Component B: 5-15 diols, 10-30 highly active polyisocyanates, 60-75 aluminum hydroxide, 3-13 modified hollow glass microspheres; The modified hollow glass microspheres are prepared by surface modification of hollow glass microspheres with a particle size of D50 = 40 μm by a coupling agent; Aluminum hydroxide is a solid particle with a particle size of D50 = 5 to 30 μm; When mixed, the mass ratio of component A to component B is 1:(0.8-1.2); In the thermal conductive adhesive layer after component A and component B are mixed and cured, the small molecule alcohol and diol participate in the cross-linking reaction of isocyanate and polyol to form a reinforced, long-chain interpenetrating network macromolecular polyurethane polymer, and the modified hollow glass microspheres (hollow, low density but non-thermal conductive) are used as the skeleton to construct the microscopic network structure in the thermal conductive adhesive layer, and the large-particle-size modified hollow glass microspheres and the small-particle-size aluminum hydroxide particles are uniformly and firmly coated. The pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres. The aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path. The components jointly form a nano-micrometer-scale interpenetrating network and a three-dimensional thermal conductive structure in the cured thermal conductive adhesive layer, so that the thermal conductive adhesive layer has a thermal conductivity of not more than 1.50 g / cm 3 Low density and high thermal conductivity of not less than 0.84W / (m•k).
[0009] A method for preparing the aforementioned low-density, high-performance thermally conductive structural adhesive for a power battery, characterized by comprising the following steps: S1: Preparation of Component A Put the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres into the reactor in sequence, heat up to 70-80°C, stir evenly, then heat up to 100-130°C, evacuate to below -90KPa and stir for 2-4h, add dehydrating agent when the temperature drops below 60°C, then continue stirring for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component A; S2: Preparation of Component B Add diol to the reactor in proportion, dehydrate at 100-130°C under vacuum below -90KPa for 2-4h, add highly active polyisocyanate after it drops below 50°C, stir and heat to 65-85°C, react for 2h-2.5h, then add aluminum hydroxide thermal conductive filler and modified hollow glass microspheres, stir for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component B; S3: Preparation of hybrid thermal conductive structural adhesive The A component and the B component are packaged separately, and when used, the A and B components are mixed evenly at a mass ratio of 1: (0.8-1.2), and then coated on the connecting surface of the aluminum shell or plastic part of the power lithium battery; S4: Preparation of thermal conductive adhesive layer It is heated and cured at room temperature or at 80°C to form a thermally conductive adhesive layer of a set thickness; the internal cross-linking reaction of the thermally conductive adhesive layer is enhanced, and the long-chain interpenetrating polyurethane polymer uses modified hollow glass microspheres as a skeleton to construct the microstructure within the thermally conductive adhesive layer, so that the pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres, and aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path; the polyurethane polymer uniformly and firmly coats the modified hollow glass microspheres and the thermally conductive filler aluminum hydroxide particles to form a long-chain interpenetrating network and a three-dimensional thermally conductive structural adhesive layer at the nano-micrometer scale, and the connecting surface is bonded and sealed. At this time, in the interpenetrating networks and three-dimensional thermal conductive microstructures of multiple nano-micrometer scales of different scale levels, large-diameter hollow glass microspheres form a spatial pore skeleton, and small-diameter aluminum hydroxide particles fill the pores in the skeleton, and then are uniformly coated, networked and fixed in position by macromolecular polymers. Aluminum hydroxide particles form a reliable and short three-dimensional thermal conductive path in the thermal conductive adhesive layer, which can significantly reduce the solid density of the thermal conductive adhesive layer while still maintaining key properties such as high thermal conductivity, high mechanical strength, high shear strength, high flame retardancy, and high weather resistance, so that the thermal conductive adhesive layer has a thermal conductivity of no more than 1.50 g / cm 3 Low density and high thermal conductivity of not less than 0.84W / (m•k).
[0010] The beneficial effects of the low-density, high-performance thermally conductive structural adhesive for power batteries and the preparation method thereof provided by the present invention include at least the following points: 1. The present invention, through the coordinated improvement of raw materials and preparation methods, introduces organic materials with unique components and proportions to polymerize into long-chain polymer materials, and introduces modified hollow glass microspheres (low-density fillers and skeletons for building microscopic network structures, shortening heat conduction paths) with suitable shape structure, scale, strength and addition amount, and multiple functions, and aluminum hydroxide, and makes each component cooperate with each other. During the curing process, the polymer materials jointly form a cross-linking reaction-enhanced, long-chain interpenetrating polymer polyurethane polymer network, and the internal microstructure is shaped with the modified hollow glass as the skeleton. The polymer network can effectively cover the inorganic thermal conductive filler aluminum hydroxide powder particles and modified hollow glass microspheres, so that the pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres, so that the cured thermal conductive adhesive layer forms a three-dimensional thermal conductive microstructure with a nano-micrometer interpenetrating network and a shorter thermal conductive path at multiple scale levels, while significantly reducing the solid density of the thermal conductive adhesive layer (which has a significant effect on the lightweight of automobile batteries) while maintaining or improving other key properties, and can maintain thermal conductivity, insulation, flame retardancy, high strength and excellent toughness, thereby overcoming the contradictory properties of the density and mechanical strength, high thermal conductivity, flame retardancy, adhesion, etc. of the thermal conductive adhesive layer, especially the thermal conductivity coefficient can still meet the design requirements, so that the thermal conductive adhesive layer has a thermal conductivity of no more than 1.50 g / cm 3 The low density and high thermal conductivity of no less than 0.84W / (m•k) can simultaneously meet the needs of electric vehicles for weight reduction and efficiency improvement.
[0011] 2. The low-density, high-performance thermally conductive structural adhesive for power batteries provided by the present invention introduces an organic material of a high molecular weight polymer that can be enhanced by a cross-linking reaction in a polymerization reaction and has long-chain interpenetrating polymers, as well as an inorganic thermally conductive filler of suitable size, addition ratio and physical and chemical properties, and a modified hollow glass microsphere that can form a multi-level (nano / micron) and network structure skeleton at different scales. Through the cooperation of each component, the thermally conductive adhesive layer finally obtained after curing has a reasonable microstructure, and the thermally conductive filler can fully fill the pores formed around the hollow glass microspheres to form a good three-dimensional thermal conductive path, so that the cured thermally conductive adhesive layer has a low density (the lowest can reach 1.33 g / cm 3 ) and high thermal conductivity, the density is more than 15% lower than similar products in the prior art, and the overall manufacturing cost is low, thus meeting the needs of electric vehicles for weight reduction, efficiency improvement and cost reduction.
[0012] 3. The present invention combines the appropriate addition amount, scale, shape, structure, compressive strength and other characteristics of the modified hollow glass microspheres to make them the core skeleton in the microscopic network structure in the thermal conductive adhesive layer, effectively shorten the three-dimensional heat conduction path around the glass microspheres, and improve the comprehensive performance of the materials such as thermal conductivity, mechanical and toughness while reducing the density. The modified hollow glass microspheres used in the present invention are treated by surface modification of the coupling agent to reduce their oil absorption value, greatly improve their interfacial adhesion to component A and other components in component B, and further combine the scale of the long-chain polymer enhanced by the cross-linking reaction and the thermal conductive filler, so that the modified hollow glass microspheres can be added in a large proportion (the addition amount can reach 10wt% or more), and the microstructure is shaped by using the modified hollow glass microspheres as the skeleton, so that the thermal conductive structural adhesive product has a lower solid density on the basis of meeting the requirements of thermal conductivity and bonding strength, and the density can be reduced by 15-20% compared with traditional products or CN114316880A, which better overcomes the technical contradiction that the thermal conductivity coefficient and mechanical strength decrease rapidly when the density decreases.
[0013] 4. The modified hollow glass microspheres used in the present invention have high compatibility with polyurethane materials, and the cured thermal conductive adhesive layer has good adhesion to a variety of substrates (including polar and non-polar substrates); and the modified hollow glass microspheres have high compressive strength and closed-pore rate, and are not easy to break during the production and construction process, so that the cured thermal conductive adhesive layer has stronger weather resistance, acid and alkali resistance, and aging resistance, and there is no risk of blistering during long-term use, so that it can meet the various requirements of new energy vehicle lithium batteries for thermal conductive structural adhesives for structural bonding.
[0014] 5. The preparation method provided by the present invention uses fewer types of components, has readily available raw materials, simple operation, mild conditions, compact process steps, easy control, easy industrial batch production and use, and has excellent industrial application prospects; the thermal conductive structural adhesive after the two components are mixed can be cured at room temperature or heated to a temperature below 80°C, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a 200 μm scale electron microscope image of a vertical cross section of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in Example 1 of the present invention; Figure 2 This is a 50 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 1 of the present invention; Figure 3 This is a 20 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 1 of the present invention; Figure 4This is a 10 μm scale electron microscope image of a vertical cross section of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in Example 1 of the present invention; Figure 5 This is a 4 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 1 of the present invention; Figure 6 This is a 500nm scale electron microscope image of a vertical cross section of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in Example 1 of the present invention; Figure 7 This is a 200 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 2 of the present invention; Figure 8 This is a 50 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 2 of the present invention; Fig. 9 This is a 10 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 2 of the present invention; Fig.10 This is a 4 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 2 of the present invention; Fig.11 This is a 500nm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 2 of the present invention; Fig.12 This is a 200 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 3 of the present invention; Fig.13 This is a 100 μm scale electron microscope image of a vertical cross section of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in Example 3 of the present invention; Fig.14 This is a 40 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 3 of the present invention; Fig.15 This is a 5 μm scale electron microscope image of a vertical cross section of a thermally conductive adhesive layer after curing of a low-density, high-performance thermally conductive structural adhesive for a power battery prepared in Example 3 of the present invention; Fig.16 This is a 500nm scale electron microscope image of a vertical cross section of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0016] The technical scheme of the present invention is described clearly and completely below in conjunction with the drawings and embodiments of the present invention. The raw materials used in the following embodiments of the present invention are all commercially available commodities; among them, cashew nut shell oil-modified polyether polyol is purchased from Cardolite; isophorone diisocyanate is purchased from Wanhua Chemical; small molecule alcohol is commercially available trimethylolpropane; aluminum hydroxide thermal conductive filler is purchased from Foshan Jinge; water remover is vinyl trimethoxysilane, purchased from Guangzhou Yourun Chemical; catalyst is organic zirconium catalyst, purchased from Guangzhou Yourun Chemical; high-activity polyisocyanate is diphenylmethane diisocyanate, purchased from Wanhua Chemical; diol is PPG polyether, purchased from Shanghai Jiahua.
[0017] Basic Example The basic embodiment of the present invention is a targeted research and development aimed at the fact that the 0.8W~1.2W polyurethane thermal conductive structural adhesive in the prior art cannot simultaneously meet the needs of weight reduction, efficiency improvement and cost reduction of new energy vehicles.
[0018] The low-density, high-performance thermally conductive structural adhesive for power batteries provided in this embodiment is made of the following components in the following proportions (by weight): Component A: polyol 20-40, small molecule alcohol 0.5-2.0, dehydrating agent 0.1-1, aluminum hydroxide 60-75, catalyst 0.01-0.10, modified hollow glass microspheres 3-13; Component B: 5-15 of diol, 10-30 of highly active polyisocyanate, 60-75 of aluminum hydroxide, and 3-13 of modified hollow glass microspheres; wherein the relative molecular weight of the diol is 1000-6000; The modified hollow glass microspheres are prepared by surface modification of hollow glass microspheres with a particle size of D50 = 40 μm by a coupling agent; Aluminum hydroxide is a solid particle with a particle size of D50 = 5 to 30 μm; When mixed, the mass ratio of component A to component B is 1:(0.8-1.2); In the thermal conductive adhesive layer after component A and component B are mixed and cured, the small molecule alcohol and diol participate in the cross-linking reaction of isocyanate and polyol to form a reinforced, long-chain interpenetrating network macromolecular polyurethane polymer, and the modified hollow glass microspheres are used as the skeleton to construct the microscopic network structure in the thermal conductive adhesive layer, and the large-particle-size modified hollow glass microspheres and the small-particle-size aluminum hydroxide particles are uniformly and firmly coated. The pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres. The aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path. The components jointly form a nano-micrometer-scale interpenetrating network and a three-dimensional thermal conductive structure in the cured thermal conductive adhesive layer, so that the thermal conductive adhesive layer has a particle size of not more than 1.50 g / cm 3Low density and high thermal conductivity of not less than 0.84W / (m•k).
[0019] The polyol is one or more of polyolefin polyol, polyacrylate polyol, cashew nut shell oil bio-based modified polyol, polymer polyol POP, and has a hydroxyl value of 112-305 mg KOH / g.
[0020] The polyolefin polyol, polyacrylate polyol, cashew nut shell oil bio-based modified polyol, and polymer polyol POP used in the present invention are all oligomer polyols, and the main difference is the different initiators and synthetic raw materials. Among them, the representative products of polyolefin polyols are terminal hydroxyl polybutadiene (butyl hydroxy), terminal hydroxyl butadiene-acrylonitrile copolymer (butyl hydroxy), etc.; polyacrylate polyol is synthesized from hydroxyl-containing acrylate or allyl alcohol and hydroxyl-free acrylate; polymer polyol POP is also known as vinyl polymer grafted polyether polyol, also known as grafted polymer polyol, which is formed by free radical grafting polymerization of vinyl monomers with parent polyoxypropylene ether polyol in the presence of an initiator, and generally has a white or light milky yellow appearance, and is a polyol containing organic fillers; cashew nut shell oil bio-based modified polyol is also called modified cashew nut shell oil polyether polyol, which is a bio-based polyol prepared by extracting cardanol from cashew trees and reacting it with formaldehyde, diethanolamine, etc. to undergo Mannich reaction, liquid, hydroxyl value 225~305 mg KOH / g.
[0021] The small molecule alcohol is selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,2-propylene glycol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propylene glycol, 1,2-pentanediol, 2,4-pentanediol, 2-methyl-1,4-butanediol, 2,2-dimethyl-1,3-propylene glycol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 2-methyl -1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,4-butanediol, 1,2-octanediol, 3,6-octanediol, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,7-dimethyl-3,6-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, hydroquinone-bis(β-hydroxyethyl) ether, trimethylolpropane and trimethylolpropane monoallyl ether, one or more thereof, with a relative molecular weight of 90 to 150.
[0022] The dewatering agent is vinyl trimethoxy silane or methyl trimethoxy silane.
[0023] The aluminum hydroxide used as the thermal conductive filler has a D50 of 5 to 10 μm, a D50 of 10 to 20 μm, or a D50 of 20 to 30 μm.
[0024] The catalyst is selected from one or more of an organic tin catalyst, an organic bismuth catalyst, an organic zinc catalyst and an organic zirconium catalyst.
[0025] The hollow glass microspheres have a particle size D50 of 40 μm, a compressive strength of 2000 to 6000 psi, and a density of 0.3 to 0.38 g / cm 3 , and the surface modification treatment is carried out as follows: (1) Dissolve 100 ml of titanate coupling agent in 900 ml of ethanol and stir evenly to obtain a coupling agent solution; (2) Add 100 g of hollow glass microspheres to the prepared coupling agent solution, stir with an electric stirrer at 60 rpm for 10 min, and then ultrasonically vibrate for 10 min; (3) Filter out the hollow glass microspheres, place them in an oven at 120°C, and react for 120 minutes to obtain coupling agent surface-modified hollow glass microspheres.
[0026] The diol is selected from one or more of polyoxypropylene glycol PPG, polytetramethylene glycol, and modified cashew shell impregnation polyether glycol. Among them, polytetramethylene glycol (also known as polytetramethylene glycol ether glycol, referred to as PTMEG, PTG, PTMG, PTMO or PTHF) is an important polymer, and its molecular formula is HO[CH2CH2CH2CH2O] n H. In various embodiments of the present invention, commercially available products such as PTMG1000 (2-functionality, molecular weight 1000±50, hydroxyl value 107-118 mg KOH / g) produced by Mitsubishi Corporation of Japan can be specifically selected.
[0027] The highly active polyisocyanate is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, naphthalene-1,5-diisocyanate and polymeric MDI.
[0028] The method for preparing the aforementioned low-density, high-performance thermally conductive structural adhesive for power batteries comprises the following steps: S1: Preparation of Component A Put the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres into the reactor in sequence, heat up to 70-80°C, stir evenly, then heat up to 100-130°C, evacuate to below -90KPa and stir for 2-4h, add dehydrating agent when the temperature drops below 60°C, then continue stirring for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component A; S2: Preparation of Component B Add diol to the reactor in proportion, dehydrate at 100-130°C under vacuum below -90KPa for 2-4h, add highly active polyisocyanate after it drops below 50°C, stir and heat to 65-85°C, react for 2h-2.5h, then add aluminum hydroxide thermal conductive filler and modified hollow glass microspheres, stir for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component B; S3: Preparation of hybrid thermal conductive structural adhesive The A component and the B component are sealed and packaged separately. When in use, the seals are removed, and the A and B components are mixed evenly in a mass ratio of 1: (0.8-1.2), and then coated on the connecting surface of the aluminum shell or plastic part of the power lithium battery; S4: Preparation of thermal conductive adhesive layer It is heated and cured at room temperature or at 80°C to form a thermally conductive adhesive layer of a set thickness; the internal cross-linking reaction of the thermally conductive adhesive layer is enhanced, and the long-chain interpenetrating polyurethane polymer uses modified hollow glass microspheres as a skeleton to construct the microstructure within the thermally conductive adhesive layer, so that the pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres, and aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path; the polyurethane polymer uniformly and firmly coats the modified hollow glass microspheres and the thermally conductive filler aluminum hydroxide particles to form a long-chain interpenetrating network and a three-dimensional thermally conductive structural adhesive layer at the nano-micrometer scale, and the connecting surface is bonded and sealed. At this time, in the interpenetrating networks and three-dimensional thermal conductive microstructures of multiple nano-micrometer scales of different scale levels, large-diameter hollow glass microspheres form a spatial pore skeleton, and small-diameter aluminum hydroxide particles fill the pores in the skeleton, and then are uniformly coated, networked and fixed in position by macromolecular polymers. Aluminum hydroxide particles form a reliable and short three-dimensional thermal conductive path in the thermal conductive adhesive layer, which can significantly reduce the solid density of the thermal conductive adhesive layer while still maintaining key properties such as high thermal conductivity, high mechanical strength, high shear strength, high flame retardancy, and high weather resistance, so that the thermal conductive adhesive layer has a thermal conductivity of no more than 1.50 g / cm 3 Low density and high thermal conductivity of not less than 0.84W / (m•k).
[0029] In the thermally conductive adhesive layer prepared in the embodiment of the present invention, there are multiple scale levels (from tens of nanometers to hundreds of micrometers) of nanometer-micrometer interpenetrating networks and three-dimensional thermal conductive microstructures. Large-diameter (thermal insulating) hollow glass microspheres form a spatial pore skeleton, so that the pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres. Small-diameter (thermal conductive) aluminum hydroxide particles fill the pores in the skeleton, and then are uniformly coated, networked and fixed by a macromolecular polyurethane polymer, so that the aluminum hydroxide particles can still form a relatively short length (smaller than the diameter of the glass microspheres) and reliable three-dimensional thermal conductive path in the thermally conductive adhesive layer. While significantly reducing the solid density of the thermally conductive adhesive layer, it can still continue to maintain key properties such as high thermal conductivity, high mechanical strength, high shear strength, high flame retardancy, and high weather resistance, so that the thermally conductive adhesive layer has a thermal conductivity of not more than 1.50 g / cm 3 It has low density and high thermal conductivity with a thermal conductivity coefficient of not less than 0.84W / (m•k), and also possesses other key comprehensive properties such as shear strength and hardness.
[0030] The embodiment of the present invention adopts a suitable addition amount, a particle size D50 = 40 μm, a compressive strength of 2000-6000 psi, and a density of 0.3-0.38 g / cm 3 The modified hollow glass microspheres are an inorganic non-metallic material, the main component of which is SiO2, which does not have the properties of thermal conductivity, electrical conductivity and electromagnetic shielding. The modified hollow glass beads used in the present invention after surface modification with coupling agents have the characteristics of high strength, low density and good material compatibility. However, the ordinary commercially available hollow glass microspheres have the problems of insufficient compressive strength, low closed-pore rate and high oil absorption value. In the process of insufficient compressive strength, the glass microspheres are fragile and cause pollution to the adhesive layer during production and construction, and the density will also increase accordingly. The closed-pore rate is low, and the adhesive layer will bubble significantly during curing, which affects the use effect of the adhesive layer. The oil absorption value is high, and the glass microspheres are difficult to add or the viscosity is high after addition, which makes construction inconvenient. Therefore, the present invention has specific requirements for the model, addition amount, particle size, compressive strength and modification treatment of hollow glass microspheres, and the technical effect can only be achieved by combining various characteristics.
[0031] The present invention adopts D50=40μm, compressive strength 2000~6000psi and density 0.3~0.38g / cm 3 The other two commercially available types have D50=30μm, compressive strength of 10000~18000psi, and density of 0.6g / cm 3 With D50=55~65μm, compressive strength 250~300psi and density 0.125~0.15g / cm 3The modified hollow glass microspheres used in each embodiment are specifically 3M products with a D50 of 40 μm, preferably S38 microspheres with a D50 of 40 μm and a density of 0.38 g / cm 3 .
[0032] The total addition amount of the modified hollow glass microspheres in each embodiment is 5% to 10%, and the density of the corresponding products after the adhesive layer is cured is 1.33 g / cm 3 ~1.50g / cm 3 , the thermal conductivity remains at around 0.9W / (m•k), while the shear strength and tensile strength are significantly improved, and the elongation at break remains within a reasonable range. Calculated at an average addition of 7wt%, the cured thermal conductive adhesive layer has a 1cm 3 The number of microbeads contained is 7.95 If the glass micro-arrangements are in an ideal state, i.e., stacked layer by layer, then 1cm 3 The number of layers that can be stacked is 250, 1cm 3 The average number of microbeads in each layer is 31,800, and the area occupied by each microbead (calculated as a square) is , which is equivalent to a square with a side length of 56μm; the minimum distance between the edges of two adjacent modified hollow glass microspheres is about 16μm, and the average distance is about 30μm, both of which are smaller than the diameter of the hollow glass microspheres themselves, which is conducive to the formation of a shorter interconnected three-dimensional thermal conductive path (less than 40μm) around them after the thermal conductive powder is filled, which is beneficial to improving the comprehensive performance of the adhesive layer.
[0033] The present invention is specifically described below with more detailed examples, test data, electron microscope images, etc. Unless otherwise specified, all proportions are by weight.
[0034] Summary of Examples 1 to 6 and Comparative Examples 1 to 3 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in Examples 1 to 6 are specific selections based on the aforementioned basic embodiments, and the difference is that the specific components and proportions (by weight) of the low-density, high-performance, thermally conductive structural adhesive for power batteries in each embodiment are as shown in Table 1 below: Table 1
[0035] Example 1 Please see attached Figures 1 to 6 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are specific selections based on the aforementioned basic embodiments. The difference is that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: The modified hollow glass microspheres are prepared in advance, comprising the following steps: (1) Dissolve 100 ml of titanate coupling agent in 900 ml of ethanol and stir evenly to obtain a coupling agent solution; (2) Take particle size D50 = 40 μm, compressive strength 2000 ~ 6000 psi, density 0.3 ~ 0.5 g / cm 3 100 g of hollow glass microspheres were added to the prepared coupling agent solution, stirred with an electric stirrer at 60 r / min for 10 min, and then ultrasonically vibrated for 10 min; (3) Filter out the hollow glass microspheres, place them in an oven at 120°C, and react for 120 minutes to obtain the desired modified hollow glass microspheres; (4) According to the ratio in Table 1, the measured polyolefin polyol, small molecule alcohol, aluminum hydroxide, catalyst and modified hollow glass microspheres are sequentially put into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-130°C, evacuated to below -90 KPa and stirred for 2-4 hours, and when the temperature drops to below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5-1 hour under a vacuum of below -90 KPa, the material is discharged, sealed and packaged, and component A is obtained; Among them, the polyol is cashew nut shell oil bio-based modified polyol, with a hydroxyl value of 225mg KOH / g; the small molecule alcohol is trimethylolpropane; the catalyst is CUCAT-GF02 of Guangzhou Yourun Chemical; the dehydrating agent is methyltrimethoxysilane; the aluminum hydroxide is a mixture of two powder products of D50=5~10μm and D50=10~20μm in a mass ratio of 2:1; (5) Add diol to the reactor, dehydrate at 100-130°C under vacuum below -90KPa for 2-4h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 65-85°C, react for 2h-2.5h, then add thermal conductive filler aluminum hydroxide and modified hollow glass microspheres, stir for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component B; Among them, the highly active polyisocyanate is diphenylmethane diisocyanate; the diol is polyoxypropylene glycol with a relative molecular weight of 1000; the aluminum hydroxide is prepared by mixing two powder products with particle sizes of D50=5-10μm and D50=10-20μm in a mass ratio of 2:1; (6) When in use, remove the packaging of the above-mentioned component A and component B, mix them evenly in a weight ratio of 1:1 to obtain a low-density polyurethane thermal conductive structural adhesive, and evenly apply it to the connecting surface of the aluminum shell or plastic part of the power lithium battery to reach a set thickness; (7) The thermal conductive adhesive layer is heated and cured at room temperature or 80°C to form a thermal conductive adhesive layer of a set thickness (generally 0.25 to 1 mm); the thermal conductive adhesive layer is internally cross-linked to form a reinforced, long-chain interpenetrating network macromolecular polyurethane polymer, and the modified hollow glass microspheres are used as the skeleton to construct the microstructure within the thermal conductive adhesive layer, and the thermal conductive filler aluminum hydroxide particles are evenly and firmly coated. The aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a long-chain interpenetrating network and a three-dimensional thermal conductive structure with a nano-micrometer scale, and the connection surface is bonded and sealed.
[0036] The embodiment of the present invention makes it possible to add a larger proportion of the modified hollow glass microspheres by appropriately adding the proportion (which can be further converted into the number of particles, the number of layers and the volume), selecting the scale and model and modifying the modified hollow glass microspheres, and makes the thermal conductive adhesive layer have a lower density on the basis of meeting the key performance requirements such as thermal conductivity and bonding strength. The experimental results show that the thermal conductivity coefficient of the low-density polyurethane thermal conductive structural adhesive provided by the embodiment of the present invention after curing is 0.80-1.0W / (m·k) and the density is 1.30-1.5g / cm 3 The tensile shear strength is 10-16 MPa (23°C, 7d), and the tensile strength is 10.0-16.0 MPa (23°C, 7d). See Table 1 for specific test results.
[0037] The cross-sectional electron microscope image of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in the embodiment of the present invention is shown in the attached figure. Figures 1 to 6 As shown, by observing the microstructure diagrams at various scales, it can be seen that the interior of the vertical cross-section of the cured thermally conductive adhesive layer is composed of a mesh macromolecular polyurethane polymer that is reinforced after the cross-linking reaction and has long-chain interpenetrating networks. The microstructure inside the thermally conductive adhesive layer is constructed with large-particle modified hollow glass microspheres as the skeleton, with the modified hollow glass microspheres as the local core and aluminum hydroxide particles filling the pores around the modified hollow glass microspheres. The polyurethane polymer then evenly and firmly coats the insulating low-density modified hollow glass microspheres and the thermally conductive filler aluminum hydroxide particles to form a three-dimensional thermally conductive structure with multi-scale nano-micrometer long-chain interpenetrating networks and shorter pathways, and the connecting surfaces are bonded and sealed. The high molecular weight polyurethane polymer material is distributed on the surface, periphery and pores of solid modified hollow glass microspheres and aluminum hydroxide particles. The components work together to form a dense three-dimensional thermal conductive microstructure with a nano-micrometer scale interpenetrating network in the three-dimensional space of the adhesive layer. The high molecular weight material and the solid particles complement each other to form a virtual-real combination of micro-network structures, which can greatly reduce the density of the thermal conductive adhesive layer and maintain the thermal conductivity, hardness, mechanical strength, flame retardancy and dielectric strength of the thermal conductive adhesive layer to meet the design requirements, thus better meeting the needs of reducing weight and increasing efficiency of electric vehicles.
[0038] The test data of the main properties and parameters of the thermal conductive adhesive layer after curing of the low-density, high-performance thermal conductive structural adhesive for power batteries prepared in this embodiment are shown in Table 2.
[0039] The test methods used in Table 2 are: Tensile strength and elongation at break: tested using the method in GB / T 528-2009; Shear strength: tested using the method in GB / T 7124-2008; Thermal conductivity: tested using the method in ASTMD 5470; Hardness: Tested using the method in GB / T 531.1-2008; Density: Tested using the method in GB / T 533-2008.
[0040] Example 2 Please see attached Figure 7-11 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: (1) According to the ratio in Table 1, the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres are sequentially added into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-120°C, vacuumed to below -90 KPa and stirred for 2.5 h, and when the temperature drops below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5 h under a vacuum below -90 KPa, the material is discharged, and sealed and packaged to obtain component A; (2) Add diol into the reactor, dehydrate at 100-120°C under vacuum below -90 KPa for 2 h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 70°C-80°C, react for 2 h-2.5 h, then add aluminum hydroxide thermal conductive filler and hollow glass microspheres, stir for 0.5 h under vacuum below -90 KPa, discharge the material, seal and package to obtain component B.
[0041] (3) The above-mentioned component A and component B are mixed evenly in a mass ratio of 1:0.8 to obtain a low-density polyurethane thermal conductive structural adhesive.
[0042] Among them, the polyol is polyolefin polyol with a hydroxyl value of 180mg KOH / g; the small molecule alcohol is 1,4-butanediol; the catalyst is CUCAT-GF02 of Guangzhou Yourun Chemical; the dehydrating agent is methyltrimethoxysilane; the high-activity polyisocyanate is diphenylmethane diisocyanate; the diol is modified cashew nut shell impregnation polyether diol with a hydroxyl value of 170mg KOH / g; and the aluminum hydroxide is a powder product with D50=10~20μm.
[0043] The low-density, high-performance thermally conductive structural adhesive for power batteries prepared in the embodiment of the present invention has a cross-sectional electron microscope image of the cured thermally conductive adhesive layer as shown in the attached figure. Figures 7 to 11 As shown, by observing the microstructure diagrams at various scales, it can be seen that inside the vertical cross-section of the cured thermal conductive adhesive layer, the polymer materials enhanced by the cross-linking reaction and interpenetrating long chains are interwoven to form a multi-level nano-micrometer network structure, and the long chains formed by the polymer materials can also span the pores between the solid particles, thereby reducing the material density and shortening the length of the heat conduction path, so that the material has key properties such as high thermal conductivity and high mechanical strength.
[0044] The performance parameter test data of the thermal conductive adhesive layer after curing of the low-density and high-performance thermal conductive structural adhesive for power batteries prepared in this embodiment are shown in Table 2.
[0045] Example 3 Please see attached Figure 12-15 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiments 1-2, except that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: (1) According to the ratio in Table 1, the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres are sequentially added into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-120°C, vacuumed to below -90 KPa and stirred for 2.5 h, and when the temperature drops below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5 h under a vacuum below -90 KPa, the material is discharged, and sealed and packaged to obtain component A; (2) Add diol into the reactor, dehydrate at 100-120°C under vacuum below -90 KPa for 2 h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 70°C-80°C, react for 2 h-2.5 h, then add aluminum hydroxide thermal conductive filler and hollow glass microspheres, stir for 0.5 h under vacuum below -90 KPa, discharge the material, seal and package to obtain component B.
[0046] (3) The above-mentioned component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a low-density polyurethane thermal conductive structural adhesive.
[0047] Among them, the polyol is polyacrylate polyol with a hydroxyl value of 225 mg KOH / g; the small molecule alcohol is 1,4-butanediol; the catalyst is CUCAT-S1015 of Guangzhou Yourun Chemical; the dehydrating agent is vinyl trimethoxysilane; the high-activity polyisocyanate is isophorone diisocyanate; the diol is modified cashew nut shell impregnation polyether diol with a hydroxyl value of 170 mg KOH / g; and the aluminum hydroxide is a powder product with a particle size of D50=20~30μm.
[0048] The low-density, high-performance thermally conductive structural adhesive for power batteries prepared in the embodiment of the present invention has a cross-sectional electron microscope image of the cured thermally conductive adhesive layer as shown in the attached figure. Figures 12 to 15 As shown, by observing the microstructure diagrams at various scales, it can be seen that inside the vertical cross-section of the cured thermal conductive adhesive layer, the polymer materials enhanced by cross-linking reactions and interpenetrating long chains are interwoven to form a multi-level nano-micrometer network structure, and the long chains formed by the polymer materials can also span the pores between the solid particles, thereby reducing the material density while also enabling the material to have key properties such as high thermal conductivity.
[0049] Example 4 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiments 1-2, except that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: (1) According to the ratio in Table 1, the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres are sequentially added into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-120°C, vacuumed to below -90 KPa and stirred for 2.5 h, and when the temperature drops below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5 h under a vacuum below -90 KPa, the material is discharged, and sealed and packaged to obtain component A; (2) Add diol into the reactor, dehydrate at 100-120°C under vacuum below -90 KPa for 2 h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 70°C-80°C, react for 2 h-2.5 h, then add aluminum hydroxide thermal conductive filler and hollow glass microspheres, stir for 0.5 h under vacuum below -90 KPa, discharge the material, seal and package to obtain component B.
[0050] (3) The above-mentioned component A and component B are mixed evenly in a mass ratio of 1:0.9 to obtain a low-density polyurethane thermal conductive structural adhesive.
[0051] Among them, the polyol is a cashew nut shell oil bio-based modified polyol with a hydroxyl value of 305mg KOH / g; the small molecule alcohol is trimethylolpropane; the catalyst is CUCAT-GF02 of Guangzhou Yourun Chemical; the dehydrating agent is vinyl trimethoxysilane; the high-activity polyisocyanate is diphenylmethane diisocyanate; the diol is a modified cashew nut shell impregnated polyether diol with a hydroxyl value of 170mg KOH / g; and the aluminum hydroxide is a powder product with a particle size of D50=10~20μm.
[0052] Example 5 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiments 1-2, except that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: (1) According to the ratio in Table 1, the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres are sequentially added into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-120°C, vacuumed to below -90 KPa and stirred for 2.5 h, and when the temperature drops below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5 h under a vacuum below -90 KPa, the material is discharged, and sealed and packaged to obtain component A; (2) Add diol into the reactor, dehydrate at 100-120°C under vacuum below -90 KPa for 2 h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 70°C-80°C, react for 2 h-2.5 h, then add aluminum hydroxide thermal conductive filler and hollow glass microspheres, stir for 0.5 h under vacuum below -90 KPa, discharge the material, seal and package to obtain component B.
[0053] (3) The above-mentioned component A and component B are mixed evenly in a mass ratio of 1:0.95 to obtain a low-density polyurethane thermal conductive structural adhesive.
[0054] Among them, the polyol is a mixture of cashew nut shell oil bio-based modified polyol and polyacrylate polyol in a mass ratio of 1:1, with a mixed hydroxyl value of 225mg KOH / g; the small molecule alcohol is 1,4-butanediol; the catalyst is CUCAT-GF02 of Guangzhou Yourun Chemical; the dehydrating agent is vinyl trimethoxysilane; the high-activity polyisocyanate is toluene diisocyanate; it is a mixture of polyoxypropylene glycol and modified cashew nut shell impregnated polyether diol in a mass ratio of 2:1, with a hydroxyl value of 132mg KOH / g; the aluminum hydroxide specification is a powder product with D50=5~10μm.
[0055] Example 6 The low-density, high-performance, thermally conductive structural adhesive for power batteries and the preparation method thereof provided in this embodiment are substantially the same as those in Embodiments 1-2, except that the specific components, proportions and preparation methods of the low-density, high-performance, thermally conductive structural adhesive for power batteries in this embodiment are as follows: (1) According to the ratio in Table 1, the measured polyol, small molecule alcohol, aluminum hydroxide thermal conductive filler, catalyst, and modified hollow glass microspheres are sequentially added into the reactor, heated to 70-80°C, stirred evenly, then heated to 100-120°C, vacuumed to below -90 KPa and stirred for 2.5 h, and when the temperature drops below 60°C, a dehydrating agent is added, and then stirring is continued for 0.5 h under a vacuum below -90 KPa, the material is discharged, and sealed and packaged to obtain component A; (2) Add diol into the reactor, dehydrate at 100-120°C under vacuum below -90 KPa for 2 h, add highly active polyisocyanate after the temperature drops below 50°C, stir and heat to 70°C-80°C, react for 2 h-2.5 h, then add aluminum hydroxide thermal conductive filler and hollow glass microspheres, stir for 0.5 h under vacuum below -90 KPa, discharge the material, seal and package to obtain component B.
[0056] (3) The above-mentioned component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a low-density polyurethane thermal conductive structural adhesive.
[0057] Among them, the polyol is polyolefin polyol with a hydroxyl value of 180mg KOH / g; the small molecule alcohol is hydroquinone-bis(β-hydroxyethyl) ether; the catalyst is CUCAT-GF02 of Guangzhou Yourun Chemical; the dehydrating agent is methyltrimethoxysilane; the high-activity polyisocyanate is diphenylmethane diisocyanate; the diol is a mixture of polyoxypropylene glycol and modified cashew nut shell impregnated polyether diol in a mass ratio of 2:1, with a hydroxyl value of 132mg KOH / g; the aluminum hydroxide is a mixture of two products with particle sizes of D50=5~10μm and D50=10~20μm in a mass ratio of 2:1.
[0058] Comparative Example The component selection and proportions of Comparative Examples 1 to 4 are shown in Table 1, and the specific selection of each component and preparation process is the same as that of Example 1.
[0059] In Comparative Examples 1 to 4, Comparative Example 1 is relative to Example 1, other raw materials remain unchanged, but component A does not contain hollow glass microspheres; Comparative Example 2 Compared with Example 1, other raw materials remain unchanged, and the amount of modified hollow glass microspheres in component B is increased; Comparative Example 3 Compared with Example 1, other raw materials remain unchanged, and unmodified hollow glass microspheres with a particle size of D50 = 30 μm are used; Comparative Example 4 Compared with Example 1, other raw materials remain unchanged, and unmodified hollow glass microspheres with a particle size of D50 = 60 μm are used.
[0060] The test results of various performance data of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 2 below.
[0061] Table 2
[0062] As can be seen from Table 2, the density of the thermally conductive adhesive layer of each embodiment is significantly reduced, while maintaining good thermal conductivity, shear strength and tensile strength, and can meet various design requirements. The performance test results of the above embodiments of the present invention show that when the total addition amount of the modified hollow glass microspheres is 5-8wt%, the comprehensive performance of the thermally conductive adhesive layer is better; the maximum total addition should not exceed 10wt%, and when the total addition amount is about 5wt%, the comprehensive performance of the thermally conductive adhesive layer is optimal.
[0063] The density of the thermally conductive adhesive layer of Comparative Example 1 increased significantly; the thermal conductivity and elongation at break of the thermally conductive adhesive layer of Comparative Example 2 decreased significantly; the density of the thermally conductive adhesive layer of Comparative Example 3 did not decrease significantly; the thermal conductivity, shear strength and tensile strength of the thermally conductive adhesive layer of Comparative Example 4 all decreased significantly.
[0064] Conventional commercially available hollow glass microspheres cannot be directly applied to the embodiments of the present invention. Conventional hollow glass microspheres are hollow structures with low density, but cannot conduct heat. Therefore, when they are directly added to the thermal conductive adhesive layer, although the material density will decrease, the thermal conductivity will also decrease rapidly, and the addition amount cannot exceed 5wt%, otherwise the thermal conductivity and the like will not meet the design requirements; in addition, since conventional hollow glass microspheres (and other similar organic material particles) are thermal insulation materials and have high oil absorption values, when the addition amount is large, the viscosity of the component is significantly increased; although the density of the thermal conductive adhesive layer is reduced, due to the poor compatibility of the resin and the glass microspheres, the thermal conductivity, shear strength, tensile strength, and elongation at break all decrease significantly with the increase in the addition amount. When the addition amount is greater than 5wt%, these key properties cannot meet the design requirements, let alone reach an addition amount of 10wt% or more.
[0065] Therefore, the amount of hollow glass microspheres added, particle size, strength and material compatibility have a key impact on the microstructure, processing technology and final performance of the final adhesive layer. If hollow glass microspheres with smaller particle size are used, the hollow part has a smaller volume and higher density, and the effect of adding them on reducing the density of the adhesive layer product is small; hollow glass microspheres with larger particle size, although the density is lower, adding a smaller amount can significantly reduce the density of the product, but due to its structural reasons (large particle size, low strength), the distribution of thermal conductive filler particles in the surrounding space is not dense, leaving a large number of pores, and cannot form an effective three-dimensional thermal conductive path, but instead causing a significant decrease in thermal conductivity; at the same time, due to the relatively large particle size of hollow glass microspheres, their compressive strength is relatively low, and during production and use, the microspheres may be damaged when subjected to strong external forces, which may damage the equipment and reduce the performance of the thermal conductive adhesive.
[0066] The thermally conductive adhesive samples prepared in the above embodiments of the present invention have been tested under confidentiality and used to manufacture a ternary lithium battery module, specifically to connect and seal the gap between two lithium battery aluminum shells. The actual test shows that the thermally conductive adhesive is better than the conventional 0.8W polyurethane thermally conductive structural adhesive (density 1.65-1.75 g / cm 3 , thermal conductivity is 0.9~1.1W / (m•k)), its density decreases by 15~20%, while the thermal conductivity remains at around 0.9W / (m•k), which better overcomes the technical contradiction that the thermal conductivity and mechanical strength decrease rapidly when the material density decreases.
[0067] In summary, the low-density, high-performance thermally conductive structural adhesive for power batteries and the preparation method thereof provided by the above embodiments of the present invention form a unique three-dimensional thermally conductive microstructure with modified glass microspheres as the skeleton, long chain interpenetration, multiple scales, and short paths by selecting components and fillers of appropriate sizes, thereby increasing the amount of modified glass microspheres used and significantly reducing the density, while maintaining the various key properties of the thermally conductive structural adhesive, so that the thermally conductive adhesive layer has a thermal conductivity of not more than 1.50 g / cm 3 The low density and high thermal conductivity of not less than 0.84W / (m•k) can meet the requirements of new energy vehicle lithium batteries for structural adhesives for weight reduction, efficiency improvement, and cost reduction.
[0068] It should be particularly pointed out that the components, ratios, particle sizes and process parameters adopted in the above-mentioned specific embodiments of the present invention are only examples. Other different implementation schemes obtained by making specific selections within the scope recorded in the embodiments of the present invention can achieve the technical effects recorded in the present invention, so the present invention will not list them one by one.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. All equivalent changes made according to the components, proportions and processes of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-density, high-performance thermally conductive structural adhesive for power batteries, characterized in that: It is made of the following components in weight ratio: Component A: polyol 20-40, small molecule alcohol 0.5-2.0, dehydrating agent 0.1-1, aluminum hydroxide 60-75, catalyst 0.01-0.10, modified hollow glass microspheres 5-10; Component B: diol 5-15, high-activity polyisocyanate 10-30, aluminum hydroxide 60-75, modified hollow glass microspheres 5-10; Wherein, the modified hollow glass microspheres are prepared by surface modification of hollow glass microspheres with a particle size of D50 = 40 μm by a coupling agent; Aluminum hydroxide is a solid particle with a particle size of D50 = 5 to 30 μm; When mixed, the mass ratio of component A to component B is 1:(0.8-1.2); In the thermal conductive adhesive layer after component A and component B are mixed and cured, the small molecule alcohol and diol participate in the cross-linking reaction of isocyanate and polyol to form a reinforced, long-chain interpenetrating network macromolecular polyurethane polymer, and the modified hollow glass microspheres are used as the skeleton to construct the microscopic network structure in the thermal conductive adhesive layer, and the large-size modified hollow glass microspheres and the small-size aluminum hydroxide particles are evenly and firmly coated. The pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres. The aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path. The components jointly form a nano-micrometer scale interpenetrating network and a three-dimensional thermal conductive structure in the cured thermal conductive adhesive layer, so that the thermal conductive adhesive layer has a particle size of not more than 1.50 g / cm 3 Low density and high thermal conductivity of not less than 0.84W / (m•k).
2. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The polyol is one or more of polyolefin polyol, polyacrylate polyol, cashew nut shell oil bio-based modified polyol, and polymer polyol POP.
3. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The small molecule alcohol is selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,2-propylene glycol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propylene glycol, 1,2-pentanediol, 2,4-pentanediol, 2-methyl-1,4-butanediol, 2,2-dimethyl-1,3-propylene glycol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, One or more of alcohol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,4-butanediol, 1,2-octanediol, 3,6-octanediol, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,7-dimethyl-3,6-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, hydroquinone-bis(β-hydroxyethyl) ether, trimethylolpropane and trimethylolpropane monoallyl ether.
4. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The dewatering agent is vinyl trimethoxy silane or methyl trimethoxy silane.
5. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: Aluminum hydroxide is a thermally conductive filler, and its particle size is one or more of D50=5-10 μm, D50=10-20 μm, and D50=20-30 μm.
6. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The catalyst is selected from one or more of an organic tin catalyst, an organic bismuth catalyst, an organic zinc catalyst and an organic zirconium catalyst.
7. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The hollow glass microspheres have a particle size D50 of 40 μm, a compressive strength of 2000 to 6000 psi, and a density of 0.3 to 0.38 g / cm 3 , and the surface modification treatment is carried out as follows: (1) Dissolve 100 ml of titanate coupling agent in 900 ml of ethanol and stir evenly to obtain a coupling agent solution; (2) Add 100 g of hollow glass microspheres to the prepared coupling agent solution, stir with an electric stirrer at 60 rpm for 10 min, and then ultrasonically vibrate for 10 min; (3) Filter out the hollow glass microspheres, place them in an oven at 120°C, and react for 120 minutes to obtain coupling agent surface-modified hollow glass microspheres.
8. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The diol is selected from one or more of polyoxypropylene diol, polytetramethylene glycol, and modified cashew nut shell impregnated polyether diol.
9. The low-density, high-performance thermally conductive structural adhesive for power batteries according to claim 1, characterized in that: The highly active polyisocyanate is selected from one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, naphthalene-1,5-diisocyanate and polymeric MDI.
10. A method for preparing a low-density, high-performance thermally conductive structural adhesive for a power battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Preparation of Component A Put the measured polyol, small molecule alcohol, aluminum hydroxide, catalyst and modified hollow glass microspheres into the reactor in sequence, heat up to 70-80°C, stir evenly, then heat up to 100-130°C, evacuate to below -90KPa and stir for 2-4h, add dehydrating agent when the temperature drops below 60°C, then continue stirring for 0.5-1h under vacuum below -90KPa, discharge and seal to obtain component A; S2: Preparation of component B Add diol to the reactor in proportion, dehydrate at 100-130℃ under vacuum below -90KPa for 2-4h, add highly active polyisocyanate after it drops below 50℃, stir and heat to 65℃-85℃, react for 2h-2.5h, then add aluminum hydroxide and modified hollow glass microspheres, stir for 0.5-1h under vacuum below -90KPa, discharge, seal and package to obtain component B; S3: Preparation of hybrid thermal conductive structural adhesive The A component and the B component are packaged separately, and when used, the A and B components are mixed evenly at a mass ratio of 1: (0.8-1.2), and then coated on the connecting surface of the aluminum shell or plastic part of the power lithium battery; S4: Preparation of thermal conductive adhesive layer The thermal conductive adhesive layer is cured at room temperature or 80°C to form a thermal conductive adhesive layer of a set thickness. The internal cross-linking reaction of the thermal conductive adhesive layer is enhanced, and the long-chain interpenetrating polyurethane polymer uses the modified hollow glass microspheres as the skeleton to construct the microstructure in the thermal conductive adhesive layer, so that the pore distance between the edges of two adjacent modified hollow glass microspheres is smaller than the diameter of the modified hollow glass microspheres, and the aluminum hydroxide particles fill the pores around the modified hollow glass microspheres to form a shorter three-dimensional thermal conductive path. The polyurethane polymer uniformly and firmly coats the modified hollow glass microspheres and the thermal conductive filler aluminum hydroxide particles to form a long-chain interpenetrating network and a three-dimensional thermal conductive structural adhesive layer at the nano-micrometer scale, and the connecting surface is bonded and sealed, so that the thermal conductive adhesive layer has a thermal conductivity of not more than 1.50 g / cm 3 Low density and high thermal conductivity of not less than 0.84W / (m•k).
Citation Information
Patent Citations
Polyurethane structural adhesive with low density and high thermal conductivity
CN114316880A
Low-density two-component polyurethane heat-conducting structural adhesive for power battery and preparation method of low-density two-component polyurethane heat-conducting structural adhesive
CN117363308A